Experimental and theoretical confirmation of the scaling exponent 2 in pyramidal load displacement data for depth sensing indentation. Issue 5 (5th August 2014) - Merle, Benoit; Maier, Verena; Durst, Karsten
Summary A series of articles by Kaupp et al. have recently been published in "Scanning, " containing erroneous claims about the curvature of pyramidal nanoindentation loading curves. The present paper recalls the theoretical reasons why, for self‐similar indenter shapes like pyramidal or conical indentations, the load scales with the indentation depth squared. Furthermore, experimental evidence for that behavior is provided for a wide variety of materials, ranging from ceramics to metals and polymers. SCANNING 36:526–529, 2014. © 2014 Wiley Periodicals, Inc.